The role of plastid genes in a heterosis effect and the formation of morphophysiological traits in sunflower plants - A. V. Usatov; M. S. Makarenko; A. A. Kovalevich; A. М. Gubaidullina (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. The problem of nucleus-plastid interactions is obviously of theoretical and practical importance. However, the lack of knowledge in this area of plant research is, for the most part, caused by difficulties in isolating the contribution of the plastome to the formation of complex morphophysiological traits from the total genotypic variability. The current study employed a convenient model for studying the fundamental problem of interaction between the nucleus and plastid genomes.Materials and methods. The genetic model incorporated chlorophylldeficient sunflower mutant lines with extranuclear inheritance, developed on the genetic basis of a single inbred line. Various traits were measured in hybrids and parents, such as growth rate, plant height, inflorescence width, 1000 seed weight, chlorophyll content, seed oil content, etc.Results and conclusion. While crossing extranuclear mutant lines with wild sunflower, a heterosis effect was observed for such traits as plant height and leaf size, regardless of the low chlorophyll content in F1 hybrids. The growth rates of hybrids depended on the crossing combination: from an 86% excess (en:chlorina-7 maternal line) to complete absence of the heterosis effect (en:chlorina-6 maternal line). The results obtained witness to a significant contribution of cytogenes to the control over the trait. The inflorescence width and 1000 seed weight in all hybrid combinations (except en:chlorina-3) had similar quantitative characteristics as in the maternal mutant lines, and significantly exceeded the paternal form (wild sunflower). Consequently, plastid genes, along with nuclear ones, participate in the expression of these phenotypic traits. As for the oil content in seeds, no heterosis effect was observed in the hybrids.